THE EFFECT OF CELEBRITY ENDORSEMENTS AND PROMOTIONS ON PURCHASE DECISIONS THROUGH PURCHASE INTEREST - Ni Luh Putu Satya Wahyuni; Ni Putu Widhia Rahayu (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study aims to examine the influence of celebrity endorsements and promotions on purchasing decisions, with purchase intention as an intervening variable among consumers of Nadia Roti Bakery Store in Bandar Lampung.METHODOLOGY - This study used a quantitative approach with a survey method. The sampling technique used purposive sampling with the criteria of respondents being at least 18 years old, having been exposed to celebrity endorsements or promotions, and having made at least one purchase. The sample size was 154 respondents determined using the Slovin formula with a 5% error rate. Data were analyzed using regression analysis and mediation tests to examine the relationship between variables.FINDING - The results showed that celebrity endorsements and promotions had a positive and significant effect on purchase intention. In addition, celebrity endorsements, promotions, and purchase intention also had a positive and significant effect on purchase decisions. The results of the mediation test showed that purchase intention was able to mediate the influence of celebrity endorsements and promotions on consumer purchasing decisions. The findings of this study indicate that the use of credible public figures and effective promotional strategies can increase consumer purchasing intention and purchase decisions